Evaluasi Kinerja Angkutan Umum Kota Malang (study kasus: Angkutan umum Kota Malang jalur HM) - Kurniawan, Achendri M. (Jurnal Qua Teknika, 2016)
Transportation is a means of accelerating the economy. Most users of public transport switch to private vehicles. The study aims to determine the performance, the optimal number in accordance with the needs of the community, and know the number of maps that can be made GIS software from the performance evaluation of public transportation in Malang. HM public transport performance assessment parameters generally have good criteria, but for load factor parameters still below national stadart that is <70%. The need for optimal public transport on the HM route is 30 units. Spatially from GIS analysis can produce 3 main map, that is dynamic load factor map, travel speed, and travel time. Besides the 3 main maps, there are still supporting maps that are road network condition map, population distribution map, and population density map. As for the frequency parameter is not included, this is because the frequency parameter is only one line or one type only.